Carbon tax: A bibliometric analysis for future research in Indonesia - Sulistiyanti, Umi; Falikhatun, Falikhatun (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This study aims to conduct a literature review of previous studies on carbon tax and explore the essential features for future research directions in carbon tax. This research is analyzed by a bibliometric method using VOS Viewer and R Studio. The Scopus database from 2013 to 2023 was explored to scrutinize the co-occurrence and co-authorship of 769 research articles. The results show that the most significant increase in the research publications on carbon tax occurred in 2022. This increase is due to the rise in the number of publications on carbon tax in developed countries, namely China, the United States, and the United Kingdom, as well as important events such as the Paris Agreement and Sustainable Development Goals (SDGs). This study provides potential directions for future carbon tax research in developing countries, especially Indonesia, which will implement a carbon tax in 2025. This study has a limitation in that it only focuses on English-language articles published in the Scopus database due to their quality and support from the previous literature reviews.